Students' mental toughness in physical education in schools: narrative literature review - Dea Meisya Nurfauziyah; Burhan Hambali; Alit Rahmat (PHEDHERAL, 2023)
This study aims to determine the results of theoretical and practical studies to determine students' mental toughness in physical education at school. A literature search was carried out using Google Scholar, then the article would be further analyzed using the PRISMA method and then identified using the Narrative Literature Review method. The results showed that the mental toughness of men was higher than that of women, while the leadership role of the PJOK teacher had on the mental toughness of students in participating in middle-class sports competitions with a percentage of 72%. It can be concluded that the higher a person's mental resilience, the level of anxiety they tend to have low.